2010
DOI: 10.1007/s00441-009-0904-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarization-activated and cyclic nucleotide-gated channels are differentially expressed in juxtaglomerular cells in the olfactory bulb of mice

Abstract: In the olfactory bulb, input from olfactory receptor neurons is processed by neuronal networks before it is relayed to higher brain regions. In many neurons, hyperpolarization-activated and cyclic nucleotide-gated (HCN) channels generate and control oscillations of the membrane potential. Oscillations also appear crucial for information processing in the olfactory bulb. Four channel isoforms exist (HCN1–HCN4) that can form homo- or heteromers. Here, we describe the expression pattern of HCN isoforms in the olf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…Therefore, the kinetic parameters that we determined suggest that MOB GCs may express a combination HCN1, HCN2, and HCN4 subunits, while HCN3 subunits predominantly contribute to I h in AOB GCs. In agreement with this possibility, all four HCN subunits are expressed in the OB, with HCN1 present in PGCs and GCs (Holderith et al, 2003; Fried et al, 2010), whereas HCN2 to HCN4 are more strongly expressed in the inner layers of the MOB (Notomi and Shigemoto, 2004). In the AOB, HCN1, HCN2, and HCN4 are moderately expressed, while HCN3 exhibits the strongest expression (Notomi and Shigemoto, 2004).…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, the kinetic parameters that we determined suggest that MOB GCs may express a combination HCN1, HCN2, and HCN4 subunits, while HCN3 subunits predominantly contribute to I h in AOB GCs. In agreement with this possibility, all four HCN subunits are expressed in the OB, with HCN1 present in PGCs and GCs (Holderith et al, 2003; Fried et al, 2010), whereas HCN2 to HCN4 are more strongly expressed in the inner layers of the MOB (Notomi and Shigemoto, 2004). In the AOB, HCN1, HCN2, and HCN4 are moderately expressed, while HCN3 exhibits the strongest expression (Notomi and Shigemoto, 2004).…”
Section: Discussionsupporting
confidence: 53%
“…This result suggests that MEG3, HCN3 and linc01105 regulate the expression of HIF-1α by post-transcriptional mechanisms. Evidence suggests that HIF-1α is expressed in several tumor types as a result of hypoxia and the expression of certain oncogenes3839, and it is involved in cell proliferation4041. Our study suggests that linc01105 influences proliferation by modulating HIF-1α protein expression.…”
Section: Discussionmentioning
confidence: 52%
“…However, it is also worth noting that increasing the excitability of the postsynaptic mitral cells by deleting the Kv1.3 Shaker channel resulted in a disturbance of the axonal targeting of presynaptic ORNs (Biju et al 2008). It should be noted that HCN channels are also expressed in both the mitral cells (Angelo & Margrie, 2011) and the juxtaglomerular cells (Holderith et al 2003; Fried et al 2010) of the olfactory bulb, so the morphological changes observed in HCN1 knockout mice (Mobley et al 2010) or in mice in which HCN4 was over‐expressed (e.g. the present study) may result from the malfunctions of any of those cells.…”
Section: Discussionmentioning
confidence: 67%